Cover Feature: Sustainable Synthesis of Nanoscale Zerovalent Iron Particles for Environmental Remediation (ChemSusChem 13/2020). Issue 13 (29th June 2020) - Monga, Yukti; Kumar, Pawan; Sharma, Rakesh K.; Filip, Jan; Varma, Rajender S.; Zbořil, Radek; Gawande, Manoj B.
Abstract : The Cover Feature shows a sustainable synthesis of nanoscale zerovalent iron (nZVI) using biological systems such as plants, fungi, and bacteria as well as their derived products that can replace energy‐intensive chemical and physical synthesis. The bio‐derived zerovalent iron has been proven an excellent candidate for the degradation and removal of pollutants, dyes, antibiotics, heavy metals, and inorganic contaminants. More information can be found in the Review by Y. Monga, P. Kumar, et al. on page 3288 in Issue 13, 2020 (DOI: 10.1002/cssc.202000290 ).